We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
468
1
avatar

justifier que xn+1 = xn − [f (xn)/ f ' (xn)]   puis que, pour la fonction f considérée ici, xn+1 = 1/2 ( xn + 5/xn  ) pour f(x)=x*x-5

 Jul 14, 2017
edited by Guest  Jul 14, 2017
 #1
avatar+27903 
+1

Have a look at https://en.wikipedia.org/wiki/Newton%27s_method for a derivation of the Newton-Raphson method.

 

Applying the technique tp f(x) = x2 - 5 we have:

 

f(x) = x2 - 5

 

f`(x) = 2x

 

xn+1 = xn - (xn2 - 5)/(2xn)

 

xn+1 = (2xn2 - (xn2 - 5))/(2xn

 

xn+1 = (2xn2 - xn2 + 5))/(2xn

 

xn+1 = (xn2 + 5))/(2xn

 

xn+1 = (x+ 5/xn)/2 

 

.

 Jul 14, 2017

15 Online Users